Inovasi Teknologi Moving Bed Biofilm Reactor dalam Pengolahan Air Limbah: Kajian Bibliometrik - Budirman, Budirman; Khaer, Ain; Kasim, Setiawan (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Wastewater treatment is essential in maintaining ecosystem balance and public health. Increasing population and industrialization generate abundant wastewater, demanding more efficient and effective treatment solutions. Biofilm technology, specifically Moving Bed Biofilm Reactors (MBBR), has been recognized as an effective method in reducing wastewater pollution. Biofilm utilizes buffer media in biological reactors to support the growth of bacteria that decompose various pollutants, including nitrogen compounds, carbon, pharmaceuticals, industrial chemicals, and other micropollutants that are key parameters of wastewater quality. MBBR increases the removal efficiency of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and nitrogen compounds through nitrification and denitrification. This study investigates the evolution of biofilm technology research for wastewater treatment with a focus on MBBR. Bibliometric analysis shows the global trends, organizations, institutions, and authors that have contributed most to MBBR research over the past decade. Data were collected from the Scopus database and analyzed using Excel, OpenRefine, Tableau, and VOSviewer. Results showed a significant increase in the number of publications related to biofilm technology and MBBR, with an annual increase of 8.43%. China was the main contributor with 1,026 publications, followed by India, Denmark, and the United States. Although MBBR is recognized as effective, more research is needed on the dynamics of the microbial community and the influence of operational variables on its performance. These findings highlight the importance of MBBR technology in wastewater treatment and provide insight into future research directions. Future research should focus on the development of new, more efficient biocarriers, in-depth understanding of microbial community dynamics in MBBRs, and optimization of operational parameters. Integration of MBBR technology with other treatment technologies is also a promising area to be explored. Keywords: Moving Bed Reactor (MBR), Wastewater treatment, Technological innovation, Bibliometric review, Biofilm reactor